Broadcast Media Campaigns and the Eradication of Female Genital Mutilation/Cutting in South-East Nigeria: Assessing Awareness, Knowledge, Perception and Health Behaviour - Nwamaka Ujunwa Nzotta (International Journal of Innovative Science and Research Technology, 2026)
Qualitative data corroborated these findings, revealing that campaign messages were infrequent, shallow, elitist, non-localised, and insufficiently targeted at rural women. The study concluded that broadcast media campaigns have not advanced the eradication of FGM/C in Nigeria. The study introduces and validates a four-driver model for sustainable FGM/C eradication: enhanced awareness, expanded knowledge base, positive perception shift, and health behaviour change.